Predicting success in naval flight officer training - Peterson, Floyd E.; Ambler, Rosalie K.; Lane, Norman E.; Booth, Richard F.; United States.; Naval Aerospace Medical Institute (U.S.) (Naval Aerospace Medical Institute, Naval Aerospace Medical Center, 1967)
The purpose of this study was to develop a system for the prediction of success or failure in the Naval Flight Officer (NFO) program for use during Basic NFO training. Two initial selection tests (an academic ability test and a mechanical comprehension test) plus two academic performance measures resulted in a multiple correlation coefficient of .45 with a dichotomous criterion of pass/attrite. Decision making regarding the retention of marginal students could be improved by use of the prediction formula generated in this study.
"Bureau of Medicine and Surgery, MF022.01.02.5002.9"--title page.
"15 February 1967."
Includes bibliographical references (page 5)
The purpose of this study was to develop a system for the prediction of success or failure in the Naval Flight Officer (NFO) program for use during Basic NFO training. Two initial selection tests (an academic ability test and a mechanical comprehension test) plus two academic performance measures resulted in a multiple correlation coefficient of .45 with a dichotomous criterion of pass/attrite. Decision making regarding the retention of marginal students could be improved by use of the prediction formula generated in this study.
Keywords: Flight training. / http://id.loc.gov/authorities/subjects/sh85049126